2022
DOI: 10.1002/bies.202100193
|View full text |Cite
|
Sign up to set email alerts
|

Electrical signalling in prokaryotes and its convergence with quorum sensing in Bacillus

Abstract: The importance of electrical signalling in bacteria is an emerging paradigm. Bacillus subtilis biofilms exhibit electrical communication that regulates metabolic activity and biofilm growth. Starving cells initiate oscillatory extracellular potassium signals that help even the distribution of nutrients within the biofilm and thus help regulate biofilm development. Quorum sensing also regulates biofilm growth and crucially there is convergence between electrical and quorum sensing signalling axes. This makes B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The significant enrichment of two-component systems (involving 23 differentially expressed genes) under TEA stress suggested that TEA could be sensed by two-component system, which then regulated gene expressions to enhance microbial adaption to adverse conditions. ABC transporters can derive energy from ATP cleavage for the transport of a variety of substances such as amino acids, vitamins and nucleotides, for both nutrition and signal communication [ 31 , 32 ], and its enrichment indicated that microbial metabolic and signaling processes might be active, thereby facilitating biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…The significant enrichment of two-component systems (involving 23 differentially expressed genes) under TEA stress suggested that TEA could be sensed by two-component system, which then regulated gene expressions to enhance microbial adaption to adverse conditions. ABC transporters can derive energy from ATP cleavage for the transport of a variety of substances such as amino acids, vitamins and nucleotides, for both nutrition and signal communication [ 31 , 32 ], and its enrichment indicated that microbial metabolic and signaling processes might be active, thereby facilitating biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…[10] On the other hand, biofilms can also be exploited in biotechnology for the production of commercially valuable compounds, in plant protection, wastewater treatment, stress protectants. [19,20] The cells can benefit via division of labor during biofilm matrix production, [21] and by integrating their collective behavior through the synthesis of signaling molecules (e.g., quorum sensing) [22] and potassium-dependent electric currents, [23][24][25] processes that will also allow the timely production of virulence factors by pathogenic microorganisms. [21] Moreover, biofilms also facilitate horizontal gene transfer between the cells via conjugation, transduction and transformation, as biofilms cannot only be formed by members of a single microbial species but can also comprise multispecies assemblages.…”
Section: Introductionmentioning
confidence: 99%